Socjalistyczna gospodarka mieszkaniowa jako zadanie administracji państwowej w okresie Polski Ludowej - Cendrowicz, Dominika (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The model of socialist housing policy in Poland, which was shaped in the post-war period, changed as a result of the transformation associated with the political system after 1989. The aim of the publication is to identify and analyse the legal regulations on the organisation and tasks of the state administration in the field of housing management in the years 1944–1989. The characteristics of the housing situation in the Polish People’s Republic and the model of the socialist housing economy, influenced by the patterns coming from the Soviet Union, will be presented. Conclusions will be formulated on the tasks of the state administration in satisfying the housing needs of citizens in the Polish People’s Republic.
Keywords: socjalizm; mieszkalnictwo; socjalistyczna gospodarka mieszkaniowa; normatywy mieszkaniowe; PRL